A CONTEMPORARY REFLECTION ON ECONOMY AND THE QUEST FOR A SIMPLIFIED LIFESTYLE: REVISITING THOREAU'S WALDEN - Dzüvichü, Khriereizhünuo; Yhome, Vitsolenuo (ShodhGyan-NU: Journal of Literature and Culture Studies, 2024)
This study examines the economic relevance of Henry David Thoreau’s philosophy and his quest for a simplified lifestyle in the context of the 21st century. Amidst the complexities of a globalized economy and the relentless pursuit of growth, Thoreau's wisdom serves as a catalyst for a critical reflection on economic ideologies and their impact on society. The study explores the complex interrelationships between money, education, and employment, challenging the narrow view that links education only to financial gain. Thoreau's call for a simple lifestyle, exemplified in his work "Walden," is analyzed in the light of contemporary research that highlights the tangible benefits of embracing simplicity for individual well-being, economics, and environmental sustainability. Additionally, the study explores the role of advertising in shaping consumer preferences, emphasizing Thoreau's call to reevaluate our needs in the face of widespread consumerism. Finally, the concept of a return to interdependent societies that prioritize self-sufficiency and social support is explored, drawing on historical examples and contemporary trends consistent with Thoreau's vision. Thoreau's philosophy provides valuable insights and guidance for navigating the challenges of the 21st century, overcoming materialism and economic dependence and promoting a more meaningful and sustainable way of life.